Educação ambiental e o teatro na história: uma experiência em Balbino, Cascavel, Ceará - Sousa, Ana Carolina Braga de (2011)
This research project as it finality develop a study about the experience of environmental education, that is find in process of construction, in the community called Balbino, what presents as district of Cascavel, located about 52 km from Fortaleza. Balbino is a coastal community marked by the fight to the possession of the territory and the resistance to the speculation of the territory, the exploration tourism, and to predatory fishing, those factors, that lead the consequent degradation of natural resources and the ecosystem of the community. The pedagogical proposition of this experience is founded in a interdisciplinary perspective, using as guiding elements the environmental education and the environmental history, propounding realize the consequences of exploration tourism in Balbino, using the research about relevant history facts to the community that refers to it social and environmental conflicts and the disordered utilization of their natural resources, and develop with the students reflections about this moment in the community, with the perspective of the implantation of a resort in their space, making questions about the transformations that can be realized in the environmental, and also the kind of development this achievement can bring to the community, reflecting about concepts like development, humans values, dissimilarity and environmental justice. We use the arts education, more specifically the theater as a methodology for enable the understanding of this context, making use of documental sources, interview with the area residents, identification of the representative places for the conservation of the community ecosystem and bibliography resources, providing the perception of the amplitude of the environmental question to the students, analyzing Balbino, and making the possibility, by that experience, the enlargement of their looks to the problem in a global proportion.